PENGARUH ELECTRONIC WORD OF MOUTH TERHADAP DESTINATION IMAGE DAN DAMPAKNYA PADA KEPUTUSAN PEMBELIAN - Anggi Agusta Tiurina Harahap; Sigit Haryono; Lukmono Hadi (Jurnal Ilmu Administrasi dan Bisnis, 2019)
The study was conducted to determine the effect of electronic word of mouth on destination image, and its impact on purchasing decisions. The population of this study were tourists of Tamansari Yogyakarta. 98 tourists were taken as research respondents. The sampling technique used systematic random sampling for an unlimited population. Data collection using a questionnaire. Path analysis is used to look for influence between variables and hypothesis testing with t test. The results showed there was a significant influence of electronic word of mouth on destination image, there was a significant effect of destination image on purchasing decisions, there was a significant effect of word of mouth on purchasing decisions, and there was a significant effect of electronic word of mouth on purchasing decisions through destination image. Taman Sari Managers must pay attention to the Destination Image attached to Taman Sari so that managers can improve domestic tourist purchasing decisions in the form of visits. Keywords: electronic word of mouth, destination image and purchasing decisions.